Folk Poetry and the Collected Self - de V. Renwick, Roger (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 1993)
Folk poetry is verse on topics which, in fact and in principle, are vital to the everyday concerns of the people who share it as makers, reciters, listeners, or readers. The genre displays many obvious formal and functional characteristics individuating it as a phenomenon, such as its preference for the language, imagery, and subjects of daily life, but in this essay I argue for the recognition of a trait that may not be so obvious: folk poetry’s attempts to simultaneously elicit thought, feeling, and action from its audience. By appealing equally to these three major dimensions of the personality, folk poetry depicts human beings as fully integrated, complete, “collected selves”. I illustrate the point with poems made by a Nottinghamshire coalminer and hospital porter, Ephraim Mugglestone (1909-1977).